Shadowlands: The rewriting of a life devoted to literature. (C.S. Lewis centenary 1898-1998) - Pérez Díez, María del Carmen (Estudios Humanísticos. Filología, 1998)
Shadowlands: The rewriting of a life devoted to literature. (C.S. Lewis centenary 1898-1998)